South-to-south mentoring as a vehicle for implementing sustainable health security in Africa - Stephanie Marie Norlock; Patrick W. Okanya; Anastasia Trataris; Michael E. Hildebrand; Jean de Dieu Baziki; Imane Belkourati; Maureen Ellis (BMC, 2021)
Abstract Background While sustainability has become a universal precept in the development of global health security systems, supporting policies often lack mechanisms to drive policies into regular practice. 'On-paper' norms and regulations are to a great extent upheld by frontline workers who often lack the opportunity to communicate their first-hand experiences to decisionmakers; their role is an often overlooked, yet crucial, aspect of a sustainable global health security landscape. Initiatives and programs developing transdisciplinary professional skills support the increased bidirectional dialogue between these frontline workers and key policy- and decisionmakers which may sustainably narrow the gap between global health security policy design and implementation. Methods The International Federation of Biosafety Associations' (IFBA) Global Mentorship Program recruits biosafety and biosecurity champions across Africa to provide local peer mentorship to developing professionals in their geographic region. Mentors and mentees complete structured one year program cycles, where they are provided with written overviews of monthly discussion topics, and attend optional virtual interactive activities. Feedback from African participants of the 2019-2020 program cycle was collected using a virtual Exit Survey, where aspects of program impact and structure were assessed. Results Following its initial call for applications, the IFBA Global Mentorship Program received considerable interest from professionals across the African continent, particularly in East and North Africa. The pilot program cycle matched a total of 62 individuals from an array of professional disciplines across several regions, 40 of which were located on the African continent. The resulting mentorship pairs shared knowledge, skills, and experiences towards translating policy objectives to action on the front lines. Mentorship pairs embraced multidisciplinary approaches to harmonize health security strategies across the human and animal health sectors. South-to-South mentorship therefore provided mentees with locally relevant support critical to translation of best technical practices to local capacity and work. Conclusion The IFBA's South-to-South Global Mentorship Program has demonstrated its ability to form crucial links between frontline biosafety professionals, laboratory workers, and policy- and decision-makers across several implicated sectors. By supporting regionally relevant peer mentorship programs, the gap between health security policy development and implementation may be narrowed.